2012
DOI: 10.5433/1679-0359.2012v33supl1p2616
|View full text |Cite
|
Sign up to set email alerts
|

Extração e exportação de nutrientes pelo híbrido de mamona Savana: I – Macronutrientes

Abstract: ResumoHíbridos de mamona de porte baixo e altamente produtivos, possivelmente necessitam de maior quantidade de macronutientes durante seu ciclo de desenvolvimento. Porém, no Brasil há carência de informações sobre extração e exportação de macronutrientes por híbridos de mamona de porte baixo, tanto no cultivo de safra como de safrinha. Objetivou-se com este trabalho avaliar a extração e a exportação de macronutrientes pelo híbrido de mamona Savana, de porte baixo, no cultivo de safra e safrinha. Os experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…In the vegetative period of both seasons, K and Mg contents in the stem of Lyra hybrid were higher than in leaves, although the opposite occurred to the other macronutrients (Table 1), as it was also observed in the Savana castor hybrid by Crusciol et al (2012a). The results show that, in the vegetative period, K and Mg are concentrated on the castor plant stem, where they are subsequently translocated to reproductive structures (Table 1) Científica, Jaboticabal, v.45, n.1, p.41-50, 2017ISSN: 1984 44 higher levels in the stem than in the leaves (Table 1).…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…In the vegetative period of both seasons, K and Mg contents in the stem of Lyra hybrid were higher than in leaves, although the opposite occurred to the other macronutrients (Table 1), as it was also observed in the Savana castor hybrid by Crusciol et al (2012a). The results show that, in the vegetative period, K and Mg are concentrated on the castor plant stem, where they are subsequently translocated to reproductive structures (Table 1) Científica, Jaboticabal, v.45, n.1, p.41-50, 2017ISSN: 1984 44 higher levels in the stem than in the leaves (Table 1).…”
Section: Resultssupporting
confidence: 51%
“…As castor growth and yield are directly related to its proper nutrition (Crusciol et al, 2012a), it is expected that a proper nutrient supply will result in grain yield increases. Therefore, studies have been conducted to assess the nutritional requirement of modern castor bean hybrids (Crusciol et al, 2012a;Crusciol et al, 2012b;Nascimento et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the cultivar BRS Energia, the mean yield is 1,800 kg ha -1 under rainfed conditions, in regions where rainfall is at least 500 mm. Regarding the nutritional requirement, Crusciol et al (2012) observed that the hybrid Savana extracted 31 to 155 kg of N, 3 to 17 kg of P, 13 to 71 kg of K, 12 to 56 kg of Ca, 4 to 28 kg of Mg and 7 to 29.5 kg of S per hectare in off season and season, respectively.…”
Section: Introductionmentioning
confidence: 99%